1992
DOI: 10.4141/cjas92-026
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of the duration of fertility in hens

Abstract: Beaumont, C. 1992. Genetic parameters of the duration of fertility in hens. Can. J. Anim. Sci. 72: [193][194][195][196][197][198][199][200][201]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
4
13
2
Order By: Relevance
“…Our heritability estimate for MD p (0.27 6 0.04) is close to the realised heritability of 0.21 obtained by , based on seven selection generations, but higher than the estimates of 0.15 obtained by Beaumont et al (1992) when averaged over estimation methods and generations. Our heritability estimate for H p (0.19) is close to the one (0.18) estimated by Beaumont (1992). The very high genetic correlations between MD, F and H found in our study were also observed by Beaumont (1992).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our heritability estimate for MD p (0.27 6 0.04) is close to the realised heritability of 0.21 obtained by , based on seven selection generations, but higher than the estimates of 0.15 obtained by Beaumont et al (1992) when averaged over estimation methods and generations. Our heritability estimate for H p (0.19) is close to the one (0.18) estimated by Beaumont (1992). The very high genetic correlations between MD, F and H found in our study were also observed by Beaumont (1992).…”
Section: Discussionsupporting
confidence: 86%
“…Our heritability estimate for H p (0.19) is close to the one (0.18) estimated by Beaumont (1992). The very high genetic correlations between MD, F and H found in our study were also observed by Beaumont (1992).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…So our question was to study the value of selection for an increased duration of the fertile period in order to reduce the frequency of the required AI. Previous results in domestic fowl have shown that selection for a longer fertile period is feasible [2,23,24]. Because of the possible negative consequences due to the genetic correlation between the duration of the fertile period and embryo death [2], an alternative model of selection for the duration of the fertile period was preferred, based on the number of hatched chicks after a single AI [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous observations in domestic fowl have established that selection favouring a longer fertile period is feasible (Pingel and of hatched chicks per hen (Pingel and Planert, 1978). An alternative model of selection based on the number of chicks hatched after artificial insemination has been proposed to overcome the negative consequences of the phenotypic and genetic correlations observed between the duration of the fertile period and embryo death (Beaumont, 1992;Beaumont et al, 1992). The number of chicks hatched depends on the number of eggs that are acceptable for incubation, the duration of the fertile period, and the probability of each embryo developing to hatching.…”
Section: Introductionmentioning
confidence: 99%